Acute effects of foam rolling vs. Vibration foam rolling on blood flow parameters in professional soccer players: a randomized crossover design - Padrón-Cabo, A.; Alonso-Calvete, A.; Radziminski, L.; Rey, E.; Lorenzo-Martínez, M. (The Journal of Strength and Conditioning Research, 2024)
The study aimed to compare the effects of foam roller (FR) and vibration foam roller (VFR) on blood flow parameters, measured by Doppler ultrasonography in professional soccer players. A randomized crossover design was used, and 10 professional soccer players participated in 3 experimental sessions: FR, VFR, and a control condition (CC). The maximum velocity (MVel) and maximum volume (MVol) blood flow parameters were measured in the common femoral artery of the dominant leg at 5 different time points as follows: before (pre), immediately after (post 0'), 10 (post 10'), 20 (post 20'), and 30 minutes (post 30') after the intervention. Both FR and VFR involved two 45-second sets with 15-second rest between sets in the quadriceps and hamstring, while CC required sitting for 240 seconds. The FR condition showed a significant increase in MVel (p < 0.01) at all time points after the intervention, and an increase in MVol (p < 0.05) only at post 0' compared with pre. The VFR condition showed a significant (p < 0.05) increase in MVel at post 0' and post 10' and an increase (p < 0.05) in MVol at post 0' compared with pre. In comparison with CC, the FR and VFR conditions presented significantly (p < 0.05) higher MVel values at post 0', post 10', post 20', and post 30' than CC. For both FR and VFR conditions, the MVol not only revealed a significant (p < 0.05) increase at post 0' but also at post 10' for VFR compared with CC. In summary, the FR and VFR interventions demonstrated a similar increase in blood flow parameters, suggesting that both strategies may accelerate physiological recovery in elite soccer players.